Ectoparasite infections on Mangrove Crabs (Scylla sp.) in soft shell crab aquaculture in Banda Aceh city, Indonesia. Issue 1 (February 2021) - Putra, D F; Ashari, R; Nurfadillah, N; Othman, N
Abstract: This research examined the prevalence and intensity rate of ectoparasites that infected mangrove crab ( Scylla sp.) at crab aquaculture area in Banda Aceh City, Indonesia. The study was conducted at three soft shell mangrove crab aquaculture in three different areas. Purposive sampling method was used within three aquaculture sites at Cot Langkeuweh, Gampoeng Blang, and Lamjabat village. The targeted organ was carapace, walk and swim leg and gill. Results showed that there were five parasites found from three family such as Zoothamnium sp. Vorticella sp., and Epistylis sp. Octolasmis sp ., and Copepoda sp. The highest prevalence rate was Epistylis sp . with value of 50-60% whereas the lowest prevalence was Zoothamnium sp . and Octolasmis sp. with its value of 20%. The highest intensity level was Octolasmis sp., and Zoothamnium sp. with value of 8-11.3 ind/species, whereas the lowest intensity was Copepoda sp . with value of 2 ind/species.